“What a difficult word!”: Teachers’ resources for teaching vocabulary during short stories reading (Revista de Psicología, 2019)
The current study aims to analyze, from a multimodal framework perspective, the strategies that teachers use to scaffold early vocabulary comprehension during book reading to three-year old children. From this perspective, we assume that vocabulary learning develops within conversational exchange frames, where infants rely both on linguistic information and on elements of the situational and non-verbal context, as well as on social support. Data corpus consists of two videotaped story-reading sequences in a kindergarten of CABA -twenty minutes per session-, which children from nearby urban-marginalized populations attend to (corpus: Rosemberg, Stein & Migdalek, 2003-2008). The intensive analysis made in a heuristic way used a categorization provided by Menti & Rosemberg (2009). Such categorization for vocabulary learning in elementary school describes the teachers’ movements that focus on vocabulary -repair, correction and amplification-. For video processing and codification, we used ELANii (Sloetjes and Wittenburg, 2008) software. The exchange sequences analysis showed that, besides linguistic elements -words, definitions, comparisons-, teachers draw upon a variety of multimodal resources -gestures, body movements and dramatizations- to amplify the vocabulary learning opportunities during the reading of short stories.
Keywords: vocabulary; kindergarten; multimodality; teachers resources